2018
DOI: 10.1039/c7fo01857f
|View full text |Cite
|
Sign up to set email alerts
|

Application of pulsed electric fields to tomato fruit for enhancing the bioaccessibility of carotenoids in derived products

Abstract: The application of pulsed electric fields (PEFs) to whole tomatoes is proposed as a pre-processing treatment to obtain purees with high health-related properties. Tomato fruit was subjected to different electric field strengths (0.4, 1.2 and 2 kV cm-1) and number of pulses (5, 18 and 30 pulses). Tomatoes were stored at 4 °C for 24 h after PEF processing and then ground and mixed with 5% olive oil. The resulting tomato-based product was subjected to in vitro gastrointestinal digestion. PEF treatments significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
2
17
1
1
Order By: Relevance
“…Moreover, the authors revealed that PEF treatment applied to tomato fruit increased the bioaccessibility of δ-carotene (2%), β-carotene (53%), lutein (125%), lycopene (137%), and γ-carotene (527%). These results strongly confirmed that PEF could lead to an easier release of carotenoids from the tomato matrix [ 49 ]. On the other hand, PEF had a negative effect on the cellular membranes of tomatoes that led to softening of the vegetable [ 50 ].…”
Section: The Use Of Non-thermal Technologies Within the Hurdle Consupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, the authors revealed that PEF treatment applied to tomato fruit increased the bioaccessibility of δ-carotene (2%), β-carotene (53%), lutein (125%), lycopene (137%), and γ-carotene (527%). These results strongly confirmed that PEF could lead to an easier release of carotenoids from the tomato matrix [ 49 ]. On the other hand, PEF had a negative effect on the cellular membranes of tomatoes that led to softening of the vegetable [ 50 ].…”
Section: The Use Of Non-thermal Technologies Within the Hurdle Consupporting
confidence: 75%
“…Recent experiments showed that PEF preprocessing applied to whole raw tomatoes ( Lycopersicum esculentum cv. Raf) increased concentrations of individual carotenoids (phytofluene, phytoene, lycopene, δ-carotene, lutein, γ-carotene, β-carotene) [ 49 ]. In particular, the concentrations of phytoene and phytofluene were increased by 178% and 131%, respectively, in tomato products treated with PEF and compared to untreated fruit.…”
Section: The Use Of Non-thermal Technologies Within the Hurdle Conmentioning
confidence: 99%
“…There are also studies in other whole products: potato (Galindo et al, 2009), apple (Soliva-Fortuny, Vendrell-Pacheco, Martín-Belloso, & Elez-Martínez, 2017), and tomato (Vallverdú-Queralt et al, 2013). However, the effect of PEF on both bioactive content and quality attributes were only studied in blueberry (Jin, Yu, & Gurtler, 2017) and tomato (González-Casado, Martín-Belloso, Elez-Martínez, & Soliva-Fortuny, 2018). As far as we know, there is no available information about the effect of PEF and post-treatment time on the phenolic content and on the quality attributes of whole carrots.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed electric fields (PEF), regarded as an emerging non-thermal treatment technology, has been used in inactivation of pathogenic microorganisms in food processing, which can also improve the colour, texture and flavour (Lee et al, 2017;Fauster et al, 2018;Tian et al, 2018) of food compared with other thermal processing approaches (Gonzalez-Casado et al, 2018). Besides, PEF techniques have been employed to modify the structures of the polymer compounds such as starch (Hong et al, 2016a(Hong et al, , 2016b and ovalbumin nanotube .…”
Section: Introductionmentioning
confidence: 99%